2013
DOI: 10.1111/nph.12499
|View full text |Cite
|
Sign up to set email alerts
|

Auxin response factor (OsARF12), a novel regulator for phosphate homeostasis in rice (Oryza sativa)

Abstract: SummaryPhosphorus (P) is crucial nutrient element for crop growth and development. However, the network pathway regulating homeostasis of phosphate (Pi) in crops has many molecular breeding unknowns. Here, we report that an auxin response factor, OsARF12, functions in Pi homeostasis.Measurement of element content, quantitative reverse transcription polymerase chain reaction analysis and acid phosphatases (APases) activity assay showed that the osarf12 mutant and osarf12/25 double mutant with P-intoxicated phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 59 publications
5
70
0
Order By: Relevance
“…This explaines the lower DM yield in Fe-enriched media when compare with media without Fe oxides. However, increasing root growth is a common plant strategy for improving P uptake in P-deficient media (Sun et al 2014, Wang et al 2014; also, it is consistent with the positive relationship between root DM and P uptake by plants in observed this work. The increase in root DM resulting from the presence of B. subtilis was independent on any factors affecting P availability in the growing medium (viz., P source or ferrihydrite).…”
Section: Resultssupporting
confidence: 77%
“…This explaines the lower DM yield in Fe-enriched media when compare with media without Fe oxides. However, increasing root growth is a common plant strategy for improving P uptake in P-deficient media (Sun et al 2014, Wang et al 2014; also, it is consistent with the positive relationship between root DM and P uptake by plants in observed this work. The increase in root DM resulting from the presence of B. subtilis was independent on any factors affecting P availability in the growing medium (viz., P source or ferrihydrite).…”
Section: Resultssupporting
confidence: 77%
“…Accordingly, some knockout lines of auxin response factor (ARF) genes impair root growth under low Pi supply. In the osarf12 and osarf12/ 25 mutants, the PR elongation was more responsive to Pi deficiency than the wild type (Wang et al, 2014b). …”
Section: Pr Response In Monocot Speciesmentioning
confidence: 95%
“…Recently, it has been reported that OsARF12 was involved in Pi homeostasis and that OsARF16 facilitated the efficient utilization of Pi in rice [28], [29]. However, the underlying mechanism linking auxin/cytokinin and Pi signaling is largely unknown.…”
Section: Introductionmentioning
confidence: 99%